2016
DOI: 10.5114/aoms.2016.62909
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between plasma angiopoietin-1, angiopoietin-2 and matrix metalloproteinase-2 in coronary heart disease

Abstract: IntroductionAngiopoietin-2 (Ang-2) plays a critical role in inducing tumor cell infiltration, and this invasive phenotype is caused by up-regulation of matrix metalloproteinase (MMP)-2. The relationship between Ang-2 and MMP-2 in atherosclerosis has not been reported yet. The aim is to measure the plasma concentrations of Ang-1, Ang-2 and MMP-2 and assess the correlation between the concentrations of these factors in coronary heart disease (CHD) patients.Material and methodsThe testing was done in a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The process and maintenance of vascular structures is through cell-cell and cell-matrix interactions [ 12 , 13 ]. Different studies have found changes in angiopoietin in different types of coronary heart disease [ 14 , 15 ]. Lee et al [ 16 ] found that, after induction of myocardial ischemia, the expression of the vascular endothelial growth factor (VEGF) and angiopoietin-2 in myocardial tissue significantly increased, reaching a peak on the third day of ischemia and, then, decreased, but Ang-1 remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…The process and maintenance of vascular structures is through cell-cell and cell-matrix interactions [ 12 , 13 ]. Different studies have found changes in angiopoietin in different types of coronary heart disease [ 14 , 15 ]. Lee et al [ 16 ] found that, after induction of myocardial ischemia, the expression of the vascular endothelial growth factor (VEGF) and angiopoietin-2 in myocardial tissue significantly increased, reaching a peak on the third day of ischemia and, then, decreased, but Ang-1 remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2 and MMP-9 expression levels have been reported in a number of human cancer cell lines and various human tumors including those of the ovary, breast, liver, bladder, skin, head and neck, uterine cervix, and lungs [1, 9, 36] and also have been reported in several disease conditions including coronary heart disease [37].…”
Section: Discussionmentioning
confidence: 99%
“…14 Ang-2 levels are higher in patients with stabile CAD to acute coronary syndrome (ACS), while Ang-1 levels remained unchanged. 15 Furthermore, in ACS, VEGF, in addition to Ang-2, and its receptor Tie-2 are increased as regulators of angiogenesis. 16 High Ang-2 levels predicted poor survival in patients with acute decompensated heart failure, 17 chronic kidney disease stages 4 to 5, 18 and older men with abdominal aortic aneurysm.…”
Section: Introductionmentioning
confidence: 99%